Indium-, Magnesium-, and Zinc-Mediated Debenzylation of Protected 1H-Tetrazoles: A Comparative Study - Behloul, Cherif; Benlahrech, Meriem; Foubelo, Francisco; Nájera, Carmen; Yus, Miguel (Synthesis, 2018)
5-Substituted 1-benzyltetrazoles are easily debenzylated to give the corresponding deprotected tetrazoles using dissolved metals under protic conditions: Mg/MeOH, In/MeOH, or Zn/MeCO2H are the procedures of choice for this transformation.
Keywords: debenzylation; magnesium; indium; zinc; tetrazoles